2009
DOI: 10.3998/ark.5550190.0010.812
|View full text |Cite
|
Sign up to set email alerts
|

2,13-Diaza[5]helicene: synthesis, theoretical calculations and spectroscopic properties

Abstract: An easy approach to the synthesis of azahelicenes is based on the photochemical cyclisation of symmetrically or asymmetrically 1,2-aryl-substituted double bonds. In the synthesis of 2,13-diaza [5]helicene, irradiation of 9-(2-pyridin-4-yl-vinyl)-benzo[h]isoquinoline yielded 2,9-diazadibenzo[a.h]anthracene together with the desired helicene, and the ratio of the two products depends on the solvent. In this paper we suggest that the ratio between the two products should not be ascribed to different transitions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…We found rather difficult to separate 4 from racemic 1 by column chromatography on silica gel and minimize its formation by varying the reaction conditions. We attempted to perform photochemical ring closure of 3 in different solvents as previous investigations on a diazapentahelicene had evidenced how this step could be preferentially directed towards the formation of the azahelicene by the use of polar solvents [ 12 ]. However, in this case, the use of acetonitrile instead of ethyl acetate resulted in the almost exclusive formation of 4 , while using dichloromethane or toluene we obtained both products with a prevalence of 4 .…”
Section: Resultsmentioning
confidence: 99%
“…We found rather difficult to separate 4 from racemic 1 by column chromatography on silica gel and minimize its formation by varying the reaction conditions. We attempted to perform photochemical ring closure of 3 in different solvents as previous investigations on a diazapentahelicene had evidenced how this step could be preferentially directed towards the formation of the azahelicene by the use of polar solvents [ 12 ]. However, in this case, the use of acetonitrile instead of ethyl acetate resulted in the almost exclusive formation of 4 , while using dichloromethane or toluene we obtained both products with a prevalence of 4 .…”
Section: Resultsmentioning
confidence: 99%
“…91 Dehaen et al prepared racemic chloro-substituted diaza [5]helicene derivative 39 in 57% yield by oxidative photocyclization of stilbenic system 38 containing two 2-chloroquinoline units, in toluene for 10 h using iodine as the oxidant and then transformed 39 to (1:1) diastereomeric mixture 40a 1,2 in 72% Scheme 9. Synthesis of Mono-and Bis-aza- [5]helicenes Investigated by Oxidative Photocyclization, Except 35b 2 , Which Was Prepared by an Acid Cyclization Process 78,86,87 Chemical Reviews yield by a Buchwald−Hartwig coupling with enantiopure (S)-αmethylbenzylamine (Scheme 11). While trying to separate the diastereomers (P,S,S)-40a 1 and (M,S,S)-40a 2 by column chromatography at 10 °C, they found that these compounds were not configurationally stable, with half-life times t 1/2 of 26 min at 25 °C (ΔG # = 22.4 kcal mol −1 for racemization) and 4.2 h at 10 °C.…”
Section: N-incorporating Helicenesmentioning
confidence: 99%
“…1,10-Phenanthroline, one of the smallest N-doped graphene fragments, has exhibited remarkable coordination ability toward a wide range of metal cations, with further efficient and selective catalytic performance. 7 Its extended skeleton (including 7,8-diazabenzo[ ghi ]perylene, 8 core-doped tetraazaperopyrenes (c-TAPP) 9 and other N-doped graphene fragments 10 ) have been achieved (Scheme 1(a)). These molecules exhibit efficient photon propagating and/or sensitive mechanical force responses.…”
Section: Introductionmentioning
confidence: 99%